Energy Literacy Education Characteristics in Gorontalo City, Indonesia: Cognitive Scale - Talha Dangkua; Yulanti Mooduto; Apris Tilome (Journal La Lifesci, 2022)
Main objective of this study assess and evaluate energy literacy cognitive in difference system schools in Indonesia, namely are general public school, general private school, islamic public school and islamic private school based on scope of study and gender. A questionnaire was designed to check the cognitive to 64 students from four different senior high school. This study used frequency distibution and independent t-test as analysis and use SPSS software for helping calculating the questionnaires. The overall energy literacy cognitive level is dominant in very poor level (59.4%). One of the reason energy literacy in very poor level cause most of the parents' educational backgrounds are high school graduates (44%), also 41% their parents' educational backgroud are elementry and junior high school and there are only 13% in university. Students in general school study about energy three times in a week than in islamic school is just twice in a week. Therefore, it seems normal when energy literacy in general school is higher (mean value 34) than in islamic school (mean value 32) and it also happened between public school and private school, which public school has 35 and private school has 30. In science class, energy literacy is higher than social class that is caused students in science class study about energy on physics subject and chemistry subject, whereas in social class students study energy on geography, but it is not much as in physics and chemistry subject.